Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1556/2006.6.2017.081
|View full text |Cite
|
Sign up to set email alerts
|

Pro-dopamine regulator, KB220Z, attenuates hoarding and shopping behavior in a female, diagnosed with SUD and ADHD

Abstract: BackgroundAddictive-like behaviors (e.g., hoarding and shopping) may be the result of the cumulative effects of dopaminergic and other neurotransmitter genetic variants as well as elevated stress levels. We, therefore, propose that dopamine homeostasis may be the preferred goal in combating such challenging and unwanted behaviors, when simple dopaminergic activation through potent agonists may not provide any resolution.Case presentationC.J. is a 38-year-old, single, female, living with her mother. She has a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 73 publications
(99 reference statements)
0
14
0
Order By: Relevance
“…Many studies have shown a relation between PIU and ADHD . Regardless of PIU, many reports indicate that ADHD is related to behavior dependence, such as substance‐related dependence and gambling dependence . Behavioral features of ADHD symptoms are said to be lack of self‐control, and it is fair to consider that such symptoms can lead to PIU.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have shown a relation between PIU and ADHD . Regardless of PIU, many reports indicate that ADHD is related to behavior dependence, such as substance‐related dependence and gambling dependence . Behavioral features of ADHD symptoms are said to be lack of self‐control, and it is fair to consider that such symptoms can lead to PIU.…”
Section: Discussionmentioning
confidence: 99%
“…[53][54][55] Regardless of PIU, many reports indicate that ADHD is related to behavior dependence, such as substance-related dependence and gambling dependence. [56][57][58] Behavioral features of ADHD symptoms are said to be lack of selfcontrol, 31,55 and it is fair to consider that such symptoms can lead to PIU. However, based on these observational studies, it is hard to understand the causal relationship of PIU and the aforementioned psychiatric symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Addiction-like behaviors such as hoarding or compulsive buying may be associated with high stress levels and the cumulative effects of neurotransmitters genetic variants, particularly DA. Therefore, when outcomes of dopaminergic activation are unsatisfaying with agonist therapy, DA homeostasis can be targetted in treating these undesirable behaviors (113). Some reports suggest that hyperdopaminergic states are observed in impulsive hoarding behavior, such as…”
Section: Neurotransmittersmentioning
confidence: 99%
“…Several different cognitive domains were shown to support a possible neurobiological overlap between other behavioral and substance addictions to shopping addiction. Compared to healthy controls, individuals with compulsive buying appear to have deterioration in spatial working memory, response inhibition and risk assessment during decision-making (120).In a case report with substance use disorder, the addition of a pro-dopamine compound KB200z to the treatment regimen significantly reduced stacking and shopping behaviors (113).…”
Section: Neuroimagingmentioning
confidence: 99%
“…These findings are supported through transcriptome analysis (the volume of messenger RNA molecules). Addictive disease (drug and non-drug (process) [22], depression [23], anxiety disorder [24], attention-deficit/hyperactivity disorder (ADHD) [25] and post-traumatic stress disorder (PTSD) [26] are all phenotypical conditions. Because these conditions share candidate genes and the co-occurring expression of neuropsychiatric conditions affecting the midbrain, ventral striatum, the term Reward Deficiency Syndrome has been coined to describe their shared etiology and pathophysiology [27].…”
mentioning
confidence: 99%